Percepção sobre a qualidade do serviço de água potável no Municìpio de Tucuruí – PA, Brasil: Das condições de oferta - Silva de Sousa, Pedro Henrique; Rego, Augusto da Gama; Silva de Jesus, Allan Jamesson (Revista AIDIS de ingeniería y ciencias ambientales: Investigación, desarrollo y práctica, 2024)
The article aims to analyze the perception of the quality of drinking water supply services in the city of Tucuruí-PA. With a focus on identifying specific phenomena and discussing the relationship between water supply at the SAA km 4 and water consumption and use in the Jaqueira neighborhood, a correlation analysis was carried out only between socioeconomic variables and then between socioeconomic variables and those of water consumption and use. The study was carried out in two stages, the first addressing the capacity of the drinking water supply sector in km4 and the second focusing on the perception of services by the population of the Jaqueira neighborhood. The research indicated that by the year 2028, the km4 system may not have the capacity to meet the water demand of the population living in the area it serves. In addition, the population of the Jaqueira neighbourhood, characterized mainly by small families, low income and low level of education, evaluates the services as poor or very poor. In addition, a negative correlation was identified between the occurrence of intermittent water supply and the assessment of water quality, a positive correlation between economic class and the use of bottled water, as well as a negative correlation between the frequency of household cleaning of reservoirs and the occurrence of symptoms related to contact with poor quality water. Finally, it was not possible to accurately identify the profile of consumers based on perception